Resources availability in basic schools in Kwara State of Nigeria: implications for instructional supervision - Fasasi, Yunus Adebunmi (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2017)
Teachers and textbooks are vital human and instructional resources, which administrators of educational institutions require for successful implementation of their educational programmes. This study investigated availability and adequacy of these resources and their implications on instructional supervision. Two research questions were answered and two hypotheses were tested in the study. Population for the study was basic school teachers in the 16 Local Government Areas of Kwara State, Nigeria. Research instrument tagged “Resource Availability Questionnaire” (RAQ) was administered to a sample of 300 teachers from 30 basic schools, which were selected using purposive and random sampling techniques. Results of data analyses showed that teachers and textbooks were not adequate, that there was no significant difference between urban and rural schools in supply of textbooks, and that there was a significant difference between urban and rural schools in supply of teachers. It was recommended that instructional supervisors should ensure proper coordination and foster cooperation among parents, community members and other stakeholders so that they could assist the Government in supply of teachers and textbooks to basic schools in the State.